Genetic parameters of production efficiency traits in Tharparkar cattle - S.S Dhakal; S.R. Chaudhary; B.L. Pander; S. Singh (Journal of Livestock Biodiversity, 2025)
The data on 303 Tharparkar cows, progeny of 13 sires calved during 1974 to 1993 maintained at Government Livestock Farm, Hisar were considered for the estimation of genetic parameters. The means for first lactation milk yield (FLY), wet average (WA), first lactation peak yield (FPY), first lactation milk yield per day of first calving interval (MCI) and first lactation milk yield per day of age at second calving (MSC) were 1300.73 Kg. 483 Kg day, 7.49 Kg/day, 2.74 Kg/day and 0.682 Kg/day, respectively. The effect of period of calving was significant (P